A novel parameter for the prediction of pedicle screw fixation in cancellous bone - A biomechanical study on synthetic foam. (May 2020) - Weidling, Martin; Oefner, Christoph; Schoenfelder, Stephan; Heyde, Christoph-E.
Highlights: Screw contact area is in relation to pull-out strength. Degree of bone compacting is in relation to insertion torque. Thread design parameter dd can qualitatively predict pull-out strength. Product of diameter and insertion torque can qualitatively predict pull-out strength. Abstract: Pedicle screw loosening is still observed in clinical practice. Therefore, the understanding of the interaction between screw and bone is evermore subject of research. However, complex relationships between screw design and anchorage are rarely examined. For this reason, it is investigated whether screw fixation is predictable by a parameter that maps the thread. Two types of pedicle screws, 6.5 mm and 7.5 mm in major diameter, respectively, are pulled out from synthetic polyurethane foam. Representative design parameters were evaluated with regard to their influence on the insertion torque and pull-out strength. A correlation between the insertion torque and the degree of compacting of the bone was observed. In addition, the pull-out strength was found to be related to the contact area of the bone-screw interface, the bone volume displaced during screwing, and the displaced diameter. The relationship between insertion torque and pull-out strength was also linear. In addition, a relational equation was derived for the pull-out strength versus the insertion torque with the major diameter as scaling factor. Thus, the pull-out strength from cancellous bone is predictable by a representative design parameter. Furthermore, the derived relation equation opens a new perspective for the evaluation of screw fixation.